The optical network control plane state of the standards and deployment. - Saha, D.
The notion of an optical control plane has rapidly ascended from being a mere concept to a detailed set of protocol standards developed with broad industry participation. In this article we present a brief overview of optical control plane architecture and the associated protocols. We then examine the business drivers and inhibitors behind the optical control plane effort, the current state of the standards, interoperability status, and the open issues that need to be resolved before widescale deployment of this new technology can begin.
Keywords: Architecture; Deployment; Interoperability status; Open issues; Optical network control plane; Protocol standards